ECONOMIC STRUCTURE AND SEIGNIORAGE: A DYNAMIC PANEL DATA ANALYSIS. (25th November 2015) - Elbahnasawy, Nasr G.; Ellis, Michael A.
Abstract : Controlling for a more comprehensive set of economic structure variables and using system generalized method of moment (GMM) dynamic panel estimation, we consider the determinants of seigniorage. While we confirm some results found in previous literature, including an inverse relationship of financial development and exchange rate management to seigniorage, we find little evidence that political instability and polarization lead to greater reliance on seigniorage. We also find robust evidence that the size of the shadow economy and natural resource rents are directly related to seigniorage, the latter result likely a result of exchange rate management. Thus, an effective strategy to reduce reliance on seigniorage is to lower the incentives to operate in the shadow economy, while exchange rate management may be counter‐productive in countries with considerable natural resource rents. ( JEL E5, O50)